Local development toward permanently sustainable low emission economy - Piotr Kulyk; Lukasz Augustowski; Anna Mroz (Institute of Economic Research (IER), 2017)
This article presents issues of rational management of energy throughout the Lubuskie province. The starting point was the idea of permanently sustainable development. The authors focused on the problem of reducing emission of polluting gases in the context of sustainable development. The results obtained were collated with other provinces and a comparative analysis was made. The aim of the article is to evaluate the changes of emission of pollutants as well as the factor affecting emission and also to indicate the directions of its reduction. Such an approach is connected with both a long and short-term horizon, which follows from the necessity of securing clean air and 'healthy atmosphere' at present as well as for future generations, taking into consideration , however , the economical, social and environmental context. In that sense, we are looking for an alternative which would secure permanent sustainability of development throughout the province. The paper analyzes different solutions to decrease the use of coal to achieve the aims of CO2 emission reduction throughout the Lubuskie province by means of an econometric model. The authors used a fixed effects model and selected statistical tests serving to evaluate and chose the right model. For evaluating the levels of penetration of different technologies considering their economical, technical and environmental characteristics, a probabilistic approach and historical data were used. Even though air pollution with gases has been dropping in the Lubuskie province since 2011, still the actions taken at the regional level are of great significance. The policy pursued by the region should include promotion of renewable sources of energy, spatial planning, or changes in the lifestyle. In the context of sustainable development, variables such as forestation, wages, number of plants, poverty threshold and population density have proven to be important.
Keywords: Q01; Q54; 330; spat Lubuskie province; CO2 reduction; sustainable development